Glial-Plug Proliferation after Inverted Internal Limiting Membrane Flap Technique for Idiopathic Macular Hole - Sławomir Cisiecki; Karolina Bonińska; Tomasz Dybek; Maciej Bednarski (Journal of Ophthalmology, 2022)
Purpose. This study aimed to analyze the effect of multiple folded internal limiting membrane (ILM) flap in the inverted ILM flap technique on postoperative outcomes of patients with full-thickness macular hole (FTMH). Methods. This retrospective study included 41 eyes of 41 patients with FTMH treated with vitrectomy using the inverted ILM flap technique. Complete ophthalmic examination was performed preoperatively, at 1 week, and at 1, 3, 6, 9, and 12 months after surgery. Results. Postoperative SD-OCT confirmed macular hole (MH) closure in all patients. The mean BCVA improved from 0.7 LogMAR (20/100) preoperatively to 0.5 LogMAR (20/63) postoperatively. In two cases, 7 days after vitrectomy, flap closure was noted. At the final visit after 12 months, the following foveal contours were noted: 14 U-shape (34.1%), 12 irregular (W-shape) (29.3%), and 6 V-shape (14.6%). We observed a type of “plug closure” in 9 (22%) eyes in which hyperproliferation was noted in one eye. Conclusions. The surgeons should be aware of potential hyperproliferation on the retinal surface after the multi-layered flap technique.